Impact of age mismatch between donor and recipient on heart transplant mortality. Issue 3 (29th December 2020) - Kumar, Abhishek; Bonnell, Levi N.; Prikis, Marios; Solomon, Richard
Abstract: The effect of donor‐to‐recipient (D‐R) age mismatch in adult heart transplant population is not clearly described, and we undertook this study to determine the impact of age mismatch on mortality. Heart transplant recipients from 2000 to 2017 were identified using the United Network of Organ Sharing database. The cohort was divided into three groups: donor age within 5 years of recipient age (Group 1), donors >5 years younger than recipient (group 2), and donors >5 years older than recipients (Group 3). We also evaluated if this finding changed by recipient age. Twenty eight thousand, four hundred and eleven patients met the inclusion criteria. Compared to group 1, the adjusted hazard ratio (aHR) for mortality for group 2 was 0.91 (0.83–0.99, p value <.039) and for group 3 was 1.36 (1.21–1.52, p value <.001); however, when looking at recipient age as continuous variable, receiving a younger heart was protective only for recipients younger than 45 years of age, and receiving a heart transplant from an older donor was detrimental only in recipients aged 25–35.